Cardiovascular Health Effects of Road Traffic Noise - Hansell,A; Cai,Y; Gulliver,J (Issues in Environmental Scienc, 2017)
This book is a comprehensive source of authoritative information for students studying pollution, and for policy-makers concerned with vehicle emissions and road traffic impacts more generally.